Endothelin signaling regulates mineralization and posttranscriptionally regulates SOST in TMOb cells via miR 126‐3p. Issue 4 (24th February 2017) - Johnson, Michael G.; Konicke, Kathryn; Kristianto, Jasmin; Gustavson, Anne; Garbo, Rachel; Wang, Xiaohu; Yuan, Baozhi; Blank, Robert D.
Abstract: Previously, our laboratory identified ECE‐1, encoding endothelin‐converting enzyme‐1 (ECE‐1), as a positional candidate for a pleiotropic quantitative trait locus affecting femoral size, shape, and biomechanical performance. We hypothesized that endothelin‐1 (ET‐1) signaling promotes osteogenesis. Exposure of immortalized mouse osteoblast (TMOb) cells to big ET‐1 increased mineralization. Following big ET‐1 treatment, we measured the secretion of insulin‐like‐growth factor‐1 (IGF1), dickkopf‐homolog‐1 protein 1 (DKK1), and sclerostin (SOST). In each case, big ET‐1 signaling changed secretion in a manner that favored increased osteogenic activity. Treatment with ECE‐1, endothelin receptor A (EDNRA), or WNT receptor antagonists inhibited the big ET‐1‐mediated increase in mineralization. In the presence of big ET‐1, message levels of Runx2, Igf1, Dkk1, and Sost are uncoupled from protein production, suggesting posttranscriptional regulation. To evaluate the role of big ET‐1 in normal bone physiology, we inhibited EDNRA signaling during mineralization in the absence of exogenous ET‐1. EDNRA blockade reduced mineralization, decreased IGF1, and increased DKK1 and SOST secretion, responses opposite to those induced by exogenous big ET‐1. Pharmacological and siRNA knockdown to inhibit ECE‐1 reduced mineralization and IGF1 secretion with decreasing DKK1 and decreasing or stable SOST secretion, suggesting a further, unknown role of ECE‐1 in osteoblast maturation. Previously we identified miR 126‐3p as a potential ET‐1‐responsive regulator of SOST in murine cells. Overexpression of miR126‐3p increased mineralization in TMOb cells and decreased SOST secretion. Osteoblasts express the ET‐1 signaling pathway and ET‐1 signaling is necessary for normal osteoblast differentiation and mineralization, acting through regulation of miRs that target osteogenic molecules. Abstract : Endothelin‐converting enzyme‐1‐dependent endothelin signaling increases mineralization in immortalized mouse pre‐osteoblast cells via mir 126‐3p regulation of sclerostin. Endothelin signaling also regulates insulin‐like‐growth factor‐1 and dickkopf‐homolog‐1 in a posttranscriptional manner.